Characteristics of Benign Prostatic Hyperplasia (BPH) Patients Undergoing Transurethral Resection of the Prostate (TURP) - Prasetyo, Zen Ary; Budaya, Taufiq Nur; Daryanto, Besut (Jurnal Kedokteran Brawijaya, 2021)
ABSTRACTBenign prostatic hyperplasia (BPH) is one of the most common diseases affecting the elderly, and Transurethral Resection of the Prostate (TURP) is a gold standard surgical procedure in BPH patients. Although the TURP rate is high, the publication of TURP profile data in Indonesia is still limited. This study aimed to determine the characteristics of BPH patients who underwent TURP atÂ Saiful Anwar General Hospital.Â This study is a descriptive study by collecting data of BPH patients who underwent TURP from January 2015 to August 2017. As many as 162 patients with BPH underwent TURP. TURP is primarily performed in patients aged 61-70 years (39.5%). Recurrent urinary retention was the most common indication for the procedure (54.9%) followed by bladder stone (21%), pharmacological therapy failure (10.5%), inguinal hernia (8%), severe LUTS (3.7%), and renal insufficiency (1.9%). As many as 94 patients (58%) have a prostate volume higher than 50 ml. Urinary retention is the most common complaint among BPH patients who underwent TURP, and recurrent urinary retention is the most common TURP indicator.